Pola Sedimentasi di Teluk Lamong, Surabaya, Jawa Timur - Fitri Indah Kuntari; Rudi Siap Bintoro; Nirmalasari Idha Wijaya (Universitas Hang Tuah, 2020)
This research to analyze sedimentation patterns in the waters of the Lamong Bay. This research was conducted in August 2018 until May 2019. The sampling of basic sediment were using sediment grab and the sampling of suspended sediment were using nansen bottle. The data used was tide data, river discharge, velocity and direction data of sediment data. The data which was obtained from survey would be processed in the Hidro – Oceanographic Laboratory of Hang Tuah University. The data includes data on grab sediment samples and until suspended sediment. For modeling sedimentation patterns was using software SMS using river discharge data and the results of processing suspended sediment. The result data from processing models in when the high tide the sediment concentration tends to be high and at low tide the concentration tends to be low. When the high tide ocean current would lead to the bay to the river and at low tide the ocean currents will flow into the river.